Improving the Capability of Voting Organizer Group Officers in Renon Village for the 2024 Elections through Integrated Technical Guidance - Kadek Devi Kalfika Anggria Wardani; R. Bagus Barend'z Amboro; Anak Agung Ngurah Eddy Supriyadinata Gorda (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
Elections are a pillar of Indonesian democracy that requires transparent, fair, and efficient organization. Based on observations, Renon Village frequently faces challenges in the implementation of elections related to the capabilities of Voting Organizer Group officers. Therefore, these issues need to be mitigated by enhancing the capabilities of Voting Organizer Group officers. This community service activity aims to improve the capabilities of Voting Organizer Group officers in conducting the 2024 elections in Renon village. The capability enhancement involves increasing the knowledge and insight of Voting Organizer Group officers in effectively conducting the voting process. The target of this community service activity is 20 Voting Organizer Group members. The method used in this activity is Participatory Rural Appraisal (PRA). The results of the service activities show that the capability of Voting Organizer Group officers in Renon village was successfully improved through technical guidance activities. The Voting Organizer Group officers in Renon Village enhanced their knowledge regarding voting procedures, the use of electronic equipment, and other technical aspects. Therefore, the positive results of this service confirm that the Integrated technical guidance approach is an effective solution to enhance the capabilities of Voting Organizer Group officers in Renon Village, contributing positively to the organization of the 2024 Elections at the local level.